The relationship between office environment and employee productivity among low level management staff at Jabatan Ketua Menteri Melaka / Nurul Hafizah Ishak - Ishak, Nurul Hafizah (Faculty of Business and Management, 2015)
This study identified the relationship between office environments and employee productivity among low level management at Jabatan Ketua Menteri Melaka. The research questions conducted define the significant relationship between office environments and employee productivity which divided into five measurement that falls under office environments. This study was conduct among low level management at Jabatan Ketua Menteri Melaka with the total respondents of 175 whom are among different grades of position. The sampling techniques being used in the study is cluster sampling techniques since the sample size has been specified among low level management staffs at Jabatan Ketua Menteri Melaka. Pearson correlation analysis conducted between each office environments elements. The five measurement involve were furniture, noise, lighting, temperature and spatial arrangements. A very weak correlation appears in between independent and dependent variable employee productivity which is noise. On the other hand, a weak correlation occurs among lighting, temperature and spatial arrangements. Besides, a moderate relationship occurs among furniture and office environment. Other than that, this study also suggest for future research to be conduct in private sector as this study only cover for government sector office environments. For further fully identifying the significant relationship between the independent variables stated in other condition and situation.